Recent Progress in the Horner-Wadsworth-Emmons Reaction - A. Bisceglia, Juan; R. Orelli, Liliana (Current Organic Chemistry, 2015)
The Horner-Wadsworth-Emmons reaction is one of the most reliable and widespread synthetic tools for the stereocontrolled construction of ethylenic bonds. The versatility of the reaction makes it a valuable synthetic tool to prepare simple as well as densely functionalized and complex molecular scaffolds. This review is devoted to the recent evolution of the reaction, which considerably widens its product scope and synthetic potential. The main recent developments on the HWE reaction presented in this work comprise novel phosphonate reagents and sequential reactions involving the HWE olefination. Interesting applications, including access to challenging or complex synthetic targets, relevant organic compounds and natural products are also highlighted.
Keywords: tandem reactions